(untitled) (Bangladesh Journal of Genetics and Biotechnology, 2008)
No abstract available. Key words: Culex quinquefasciatus; larval size; pupal size; male mate choice tests; homoeothermic hosts; poikilothermic hosts Bangladesh j. genet. biotechnol. 6 (1&2): 19-22, 2005 (June & December)